Kebijakan Pemerintah terhadap Front Pembela Islam (FPI) Pascaperistiwa 212 Tahun 2016-2021 - Putri, Gustri Eni (State Islamic Institute of Kudus (IAIN Kudus), 2022)
This study discussed the policies of the Indonesian government in dealing with the Islamic Defenders Front (FPI) after the events of 212 from 2016 to 2021. The purpose of this study is to understand the state's attitude towards these movements, both in terms of repression strategies and tactics used to suppress social movements. , because of that the government carried out repression against FPI after the incident. year 212. Meanwhile, the method used in this paper is a case study type or model as part of a qualitative research using the concept of state repression against FPI after the events of 212. The data to be used is through a literature study from books, journals, and media reports, as well as official sources belonging to the government and social movements that are the object of study in this research. In reviewing state policy towards the Islamic Defenders Front movement, Boykoff's approach. The results of this study are the Jokowi government's policy of carrying out a repressive strategy against the FPI to drain resources (resource depletion) by committing violence against activists, detaining, and making extraordinary, stigmatizing, and intimidating rules and laws.